Effect of exogenous silicon on resistance of asparagus bean rust and its physiological mechanism - LI Guo-jing; LIU Yong-hua; ZHU Zhu-jun; WU Xiao-hua; WANG Bao-gen (浙江大学学报. 农业与生命科学版)
The effects of root-applied silicon and inoculation with Uromyces vignae on the activities of peroxidase (POD), catalase (CAT), ascorbate peroxidase (APX), phenylalanine ammonia-lyase (PAL), superoxide dismutase (SOD), the content of malonyldialdehyde (MDA), the chlorophyll fluorescence parameters and the respiration rate in the leaves of asparagus bean (Vigna sesquipedalis Wight.) were investigated. The results showed that exogenous silicon significantly increased the content of SiO2, increased the activities of antioxidant enzymes, decreased the content of MDA, delayed and inhibited the decrease of Fv/Fm, ΦPS Ⅱ and ETR, maintained higher total respiration (Vt), the alternative pathway capacity (Valt) and the alternative pathway activity (ρValt) in the leaves of susceptible cultivar inoculated with U. vignae. Without inoculation, exogenous Si couldn't affect those parameters above for susceptible variety except the activities of POD and CAT. For the resistant cultivar, Si considerably increased the activities of POD, CAT and SOD, decreased the content of MDA in the inoculated leaves, but did not affect other parameters without U. vignae inoculation. Si did not change POD isoforms pattern in both cultivars. Si significantly decreased disease index and improved the ability of resistance to rust for the susceptible variety.